Association between poor drug adherence and undernutrition among adult HIV patients in southern Ethiopia: an institution based cross sectional study - Muluken Bekele Sorrie; Nigus Kabtu Belete; Tesfaye Feleke Gadore; Darik Temesgen Assefa; Manaye Yihune Teshale; Eshetu Zerihun Tariku (BMJ Open)
Objective Undernutrition is a common issue for HIV and other immune suppressed patients. Approximately 462 million people worldwide living with HIV are experiencing undernutrition, with sub-Saharan Africa having the highest prevalence. Good adherence to antiretroviral therapy (ART) indirectly helps prevent undernutrition by suppressing viral load, increasing CD4 count, preventing viral resistance, enhancing immune reconstitution and delaying disease progression in HIV patients. This study aims to assess the association between poor drug adherence and undernutrition among adult HIV patients in southern Ethiopia.Study design An institution based cross sectional study design was used.Setting and participants The study was conducted in 406 randomly selected adult HIV patients from Gamo zone public health facilities.Primary and secondary outcomes The data were collected by a trained data collector using a structured interviewer administered questionnaire, patient record review and physical measurements. Binary logistic regression was run to select candidate variables, and a multivariable logistic regression model was used to assess the association between undernutrition and poor drug adherence, as well as other variables. A p value <0.05 with 95% CI was considered statistically significant.Results The magnitude of undernutrition was 28% (95% CI 24.0 to 33). Being a male patient (AOR 2.0, 95% CI 1.243 to 3.573), poor ART drug adherence (AOR 3.6, 1.815 to 7.428) and consuming <5 food groups (AOR 4.8, 2.901 to 8.265) were significantly associated with undernutrition among adult HIV patients.Conclusions Poor drug adherence was significantly associated with undernutrition. Also, sex and dietary diversity were identified as predictors for undernutrition among adult HIV patients. Therefore, effectively managing poor drug adherence, nutritional supplements and communicating behavioural change implications are critical for successfully preventing undernutrition.